Nanoemulsions for "Nose-to-Brain" Drug Delivery - Maria Cristina Bonferoni; Silvia Rossi; Giuseppina Sandri; Franca Ferrari; Elisabetta Gavini; Giovanna Rassu; Paolo Giunchedi (MDPI AG, 2019)
The blood⁻brain barrier (BBB) plays a fundamental role in protecting the brain from toxic substances and therefore also controls and restricts the entry of therapeutic agents. The nasal administration of drugs using the nose-to-brain pathway allows direct drug targeting into the brain, avoiding the first-pass effect and bypassing the BBB. Through the nasal route, the drug can access the brain directly along the trigeminal and olfactory nerves, which are located in the upper part of the nasal cavity. Nanoemulsions are formulations belonging to the field of nanomedicine. They consist of emulsions (commonly oil in water) stabilized by one or more surfactants—and eventually co-surfactants—delivered in droplets of small dimensions (sizes of 100⁻300 nm or less) with a high surface area. A mucoadhesive polymer such as chitosan can be added to the formulation to impair rapid nasal clearance. Nanoemulsions represent promising formulations to deliver drugs directly into the brain through the intranasal route. Therefore, they can be used as a possible alternative to oral administration, avoiding problems such as low solubility in water, poor bioavailability, enzymatic degradation and slow onset of action. This review focuses the present situation in literature regarding the use of nanoemulsions for nose-to-brain targeting, with particular attention to recent publications. Nasal nanoemulsions appear to be effective, non-invasive and safe drug delivery systems to achieve brain targeting for the treatment of neurological diseases.